Listening to children : a practitioner's guide - McLeod, Alison, 1950- (Jessica Kingsley Publishers, 2008)
'Listening to children' is one of those feel-good phrases that always features in childcare literature as if it were self-evidently a good thing. Often, however, there is a lack of critical attention to what it really means: How does one listen? How can one evidence that listening has taken place?. Starting with an introduction to the policy and practice of listening to children and young people, both individually and in groups, this practitioner's guide provides a range of practical techniques for effective listening, encompassing observation and communication, seeing things from the child's.